Model Layanan E-Konseling Dengan Media Surat Elektronik Pada Laboratorium Bimbingan Konseling Islam Fakultas Ushuluddin, Adab Dan Dakwah Iain Palangka Raya - Safitri, Arini (Jurnal Bimbingan dan Konseling Pandohop, 2021)
Abstract E-Counseling service is an alternative service in helping client problems, namely by utilizing technology, such as through the media website, electronic mail (e-mail), telephone, video, and other social networks. Technology as one of the media that can make it easier for the counselor to help the counselee (client), which is where the client can more freely and comfortably tell all his problems to the counselor without feeling ashamed or afraid of being judged by the problems the client has experienced. This study has the following objectives: (1) To describe the administration and procedures in the e-counseling process using electronic mail at the Islamic Counseling Guidance Laboratory of FUAD IAIN Palangka Raya; (2) To determine the acceptability of users and experts in the E-Counseling Service Model Using Electronic Mail Media at the Islamic Counseling Guidance Laboratory of FUAD IAIN Palangka Raya. This research produces a guidebook for e-counseling services with electronic mail media at the Islamic Counseling Guidance Laboratory of FUAD IAIN Palangka Raya, as well as a service model based on the aspects of usability, feasibility, accuracy and possibility of doing it ready for use with a slight improvement in further model development according to comments , advice and improvements from experts and practitioners.